Activated protein C inhibits lipopolysaccharide‐mediated acetylation and secretion of high‐mobility group box 1 in endothelial cells - Cai, Xiaofeng; Biswas, Indranil; Panicker, Sumith R.; Giri, Hemant; Rezaie, Alireza R. (Journal of thrombosis and haemostasis, 2019)
Essentials APC elicits cytoprotective responses in endothelial cells via EPCR‐dependent cleavage of PAR1. APC inhibits LPS‐mediated translocation and extracellular secretion of HMGB1 in endothelial cells. Signaling activity of APC inhibits LPS‐mediated acetylation of HMGB1 by epigenetic mechanisms. APC inhibits LPS‐mediated HMGB1 expression in CD31‐positive endothelial cells in cremaster muscle. Summary Background Activated protein C (APC) inhibits high‐mobility group box 1 (HMGB1) signaling and its lipopolysaccharide (LPS)‐mediated release by endothelial protein C receptor (EPCR)‐dependent activation of protease‐activated receptor 1 (PAR1) in endothelial cells. Post‐translational acetylation is known to modulate the subcellular localization of HMGB1, and its hyperacetylated form is translocated to the cytoplasm of innate immune cells before being secreted into the extracellular space. Objective To determine whether APC inhibits LPS‐mediated HMGB1 secretion from endothelial cells by modulating its acetylation status. Methods The subcellular localization of HMGB1 in LPS‐treated endothelial cells was monitored in the absence and presence of APC by western blot analysis of fractionated cell lysates and confocal immunofluorescence microscopy. Results Both western blot and immunofluorescence data indicated that APC effectively inhibits LPS‐mediated translocation of HMGB1 from the nucleus to the cytoplasm by EPCR‐dependent and PAR1‐dependent mechanisms. When EPCR was ligated by the Gla‐domain of protein C/APC, thrombin also inhibited LPS‐mediated HMGB1 translocation. Further studies revealed that APC inhibits the translocation of HMGB1 from the nucleus to the cytoplasm by inhibiting LPS‐mediated hyperacetylation of HMGB1 by (de)acetylating enzymes. Furthermore, the translocated HMGB1 was found to be associated with lysosome‐associated membrane protein 1 in LPS‐treated endothelial cells. The in vivo relevance of these findings was investigated in the mouse cremaster muscle, and this demonstrated that both wild‐type APC and a signaling‐selective mutant of APC inhibit LPS‐mediated HMGB1 expression and translocation in CD31‐positive endothelial cells. Conclusion These results suggest that APC inhibits LPS‐mediated cytoplasmic translocation and secretion of HMGB1 in endothelial cells by epigenetic mechanisms.